Features of Magnetocaloric Effect in Er(Co-Fe)2 Laves Phases - Anikin, M.S.; Tarasov, E.N.; Kudrevatykh, N.V.; Semkin, M.A.; Volegov, A.S.; Inishev, A.A.; Zinin, A.V. (KnE Materials Science, 2016)
In this work the results of measurements of heat capacity (CP) and magnetocaloric effect (MCE) in Er(Co1-хFeх)2 system in the concentration range 0.07 ≤ x ≤ 0.80 are presented. Phase composition was controlled by X-ray difraction analysis. Heat capacity was measured in the temperature range 77-320 K. MCE has been studied within the temperature range 5-670 K in magnetic fields up to 70 kOe. It was found that Fe concentration increase caused the table-like (plateau) MCE temperature dependence for both magnetic entropy change date and direct ∆T-effect measurements independently on Fe concentration. The possible reasons of such behavior are discussed.